1995
DOI: 10.1002/jmv.1890470417
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of hepatitis E virus in the Egyptian Nile Delta

Abstract: The seroendemicity of hepatitis E virus (HEV) in an entire village population located in the Egyptain Nile Delta is described. Serum specimens were obtained from 68% of the total population of 1,850 villagers. The lack of serum specimen was greatest in the youngest age group (< 5). Commercially available enzyme immunoassays (EIA) for antibody to hepatitis A virus (anti-HAV), to hepatitis B virus core antigen (anti-HBc), to second-generation hepatitis C virus (anti-HCV) core and nonstructural antigen, and to he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 17 publications
4
21
0
Order By: Relevance
“…The results showed that HEV infection is endemic, acquired early in life and its seroprevalence rate increased steadily with age, reaching 7.3% in young adults. The patterns of increase are similar to those reported in many other studies from different endemic countries [10,[15][16][17][18][19][20][21]. In north India, a region with high endemicity for HEV infection, exposure to HEV was shown to occur in early life and seropositivity for anti-HEV IgG increased progressively from 7.2%-14.2% in infancy to 33.3%-38.0% by 10 years of age in rural and urban children respectively [10].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results showed that HEV infection is endemic, acquired early in life and its seroprevalence rate increased steadily with age, reaching 7.3% in young adults. The patterns of increase are similar to those reported in many other studies from different endemic countries [10,[15][16][17][18][19][20][21]. In north India, a region with high endemicity for HEV infection, exposure to HEV was shown to occur in early life and seropositivity for anti-HEV IgG increased progressively from 7.2%-14.2% in infancy to 33.3%-38.0% by 10 years of age in rural and urban children respectively [10].…”
Section: Discussionsupporting
confidence: 88%
“…In north India, a region with high endemicity for HEV infection, exposure to HEV was shown to occur in early life and seropositivity for anti-HEV IgG increased progressively from 7.2%-14.2% in infancy to 33.3%-38.0% by 10 years of age in rural and urban children respectively [10]. A similar epidemiological picture was also seen in other studies from Turkey [17,18], Saudi Arabia [19], Egypt [20] and Mexico [21]. A study by Kamel et al on the seroepidemiology of HEV infection in an entire village population located in the Egyptian Nile delta showed seropositivity of 5.19% in the age group < 5 years, increasing progressively and peaking at 33.33% in the age group 20-24 years [20].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…6 In Egypt, where outbreaks of hepatitis E have not been noted, reports have indicated that HEV infection is, nonetheless, endemic, with community seroprevalence as high as 60%. 7,8 However, until now, there have not been any large studies to confirm these unusually high estimates. Here, we report a population-based study of anti-HEV prevalence in two communities in different regions of Egypt.…”
Section: Introductionmentioning
confidence: 96%
“…z % found in our population of long-term expatriates is situated between figures from serosurveys of populations in endemic areas such as Egypt with 17.2% (Kame1 et al 1995) and nonendemic areas such as Australia with 0.4% (Moaven et al 1995).…”
Section: 8%mentioning
confidence: 51%